Consuming Music Together Social and Collaborative Aspects of Music Consumption Technologies - O'Hara, Kenton; Brown, Barry; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Listening to, buying and sharing music is an immensely important part of everyday life. Yet recent technological developments are increasingly changing how we use and consume music. This book collects together the most recent studies of music consumption, and new developments in music technology. It combines the perspectives of both social scientists and technology designers, uncovering how new music technologies are actually being used, along with discussions of new music technologies still in development. With a specific focus on the social nature of music, the book breaks new ground in bringing together discussions of both the social and technological aspects of music use. Chapters cover topics such as the use of the iPod, music technologies which encourage social interaction in public places, and music sharing on the internet. A valuable collection for anyone concerned with the future of music technology, this book will be of particular interest to those designing new music technologies, those working in the music industry, along with students of music and new technology.
Consuming Music Together: Introduction and Overview -- Music and Emotion in Real Time -- Sharing Music -- Sharing and Listening to Music -- Social Practices Around Itunes -- Choosing Music -- Distributing the Process of Music Choice in Public Spaces -- Promoting Social Interaction in Public Spaces: The Flytrap Active Environment -- Mobile Music -- Investigating the Culture of Mobile Listening: From Walkman to iPod -- Tuna: Socialising Music Sharing on the Move -- Car Drivers Using Sound Pryer - Joint Music Listening in Traffic Encounters -- Music and Dance -- Digital Dance Hall: The Fan Culture of Dance Simulation Arcade Games -- "Sort Drugs Make Mates": The Use and Meaning of Mobiles in Dance Music Club Culture -- hpDJ: An Automated DJ with Floorshow Feedback -- Consumption as Production -- Interaction, Experience and the Future of Music -- Hail to the Thief: The Appropriation of Music in the Digital Age.
Keywords: COMPUTER SCIENCE; ARCHITECTURAL DESIGN; MUSIC; SOCIOLOGY; COMPUTER SCIENCE; COMPUTER SCIENCE, GENERAL; USER INTERFACES AND HUMAN COMPUTER INTERACTION; INTERACTION DESIGN; MUSIC; SOCIOLOGY; PERSONALITY & SOCIAL PSYCHOLOGY